The effect of vitamin d supplementation on cardiometabolic risk factors and health-related quality of life among urban vitamin d deficient premenopausal women: a randomised controlled trial / Mazliza Ramly - Mazliza , Ramly (2016)
Recent evidence has demonstrated that vitamin D deficiency is associated with cardiometabolic risk factors such as hypertension, diabetes mellitus, and hypercholesterolaemia, along with its pivotal role in musculoskeletal diseases. However, there remains a lack of randomised controlled trials required to establish causality between vitamin D and cardiometabolic risk factors. The aim is to determine whether Vitamin D supplementation in urban premenopausal women with vitamin D deficiency could improve cardiometabolic risk factors and health-related quality of life (HRQOL). A double-blind randomized controlled trial was conducted in Kuala Lumpur, Malaysia. A total of 192 premenopausal women were randomly selected to receive either placebo (n = 99) or vitamin D supplements of 50,000 IU once a week for two months and then 50,000 IU monthly for 10 months (n = 93). The participants were vitamin D deficient (< 50 nmol/l) at baseline. Primary outcomes were serum 25(OH)D, serum lipid profiles, blood pressure, and HOMA-IR, all of which were measured at baseline and at six and 12 months. HRQOL was assessed with SF-36 at baseline and 12 months. Ninety three and 99 women were randomised into the intervention and placebo groups, respectively. After 12 months, significant differences were found between the intervention and placebo groups in terms of serum 25(OH)D concentration (mean difference: 49.54; 95% CI: 43.94 to 55.14 nmol/l) and PTH levels (mean difference: -1.02; 95% CI: -1.67 to -0.38 pmol/l). There was no effect of vitamin D supplementation on HOMA-IR, serum lipid profiles or blood pressure (all p > 0.05) between the two groups. There was a small but significant improvement in the HRQOL components of vitality (mean difference: 5.041; 95% CI: 0.709 to 9.374) and mental component summary score (mean difference: 2.951; 95% CI: 0.573 to 5.329) in the intervention group compared to the placebo group. In conclusion, large and less frequent dosages of vitamin D supplementation were effective to improve vitamin D deficiency to vitamin iv D sufficiency. However, there was no improvement in measured cardiometabolic risk factors in premenopausal women. On the other hand, vitamin D supplementation appeared to improve some components of HRQOL. Longitudinal studies may be needed to establish causality between vitamin D and cardiometabolic risk factors and HRQOL.